Assessment Capability and Student Self-regulation: The Challenge of Preparing Teachers - Hill, Mary F.; Ell, Fiona R.; Eyers, Gayle (Frontiers in Education, 2017)
Research over several years has found that “effective learners tend to monitor and regulate their own learning and, as a result, learn more and have greater academic success in school” (Andrade, 2010, p.90). In New Zealand primary schools the primary purpose of assessment and evaluation is to improve students’ learning and teachers’ teaching as both respond to the information it provides. To bring this purpose to fruition teachers need to be educated to facilitate genuine engagement by learners in assessment processes; known in New Zealand as having assessment capability. In this study we investigated to what extent, and how, teacher candidates learn to involve their students in formative assessment of their own work. Participants were a cohort of undergraduate, elementary school teacher candidates in a three-year undergraduate program taught across three campuses at one university in New Zealand. Surveys and interviews were used to investigate assessment capability. Although the survey results suggested the teacher candidates may be developing such capability, the interviews indicated assessment capability was indeed an outcome of the program. Our findings demonstrate that these teacher candidates understood the reasons for involving their students and are beginning to develop the capability to teach and use assessment in these ways. However, developing assessment capability was not straight forward and the findings demonstrate that more could have been done to assist the teacher candidates in seeing and understanding how to implement such practices. Our data indicates that a productive approach would be to partner teacher candidates with assessment capable teachers and with university lecturers who likewise support and involve the teacher candidates in goal setting and monitoring their own learning to teach.